PERAN KOPING DAN ADAPTASI TERHADAP KEPATUHAN PENGOBATAN TUBERKULOSIS DI PUSAT KESEHATAN : A LITERATURE REVIEW - Larasati, Anggelisa; Yulanda, Nita Arisanti; Budiharto, Ichsan (ProNers, 2015)
Background: Tuberculosis patients have a process of controlling stimuli such as emotional distress due to disease diagnosis, anger, and self-isolation, this behavior can lead to non-compliance in the treatment. Patients with tuberculosis can have a disability in adaptation both at home and the environment in which they live. So that tuberculosis patients need the right coping assistance and the adjustment or adaptation in tuberculosis patients. Objective: To find out the role of coping and adaptation to the compliance of the treatment of pulmonary tuberculosis patients in the Health Service Center. Methods: Literature review of the role of coping and adaptation to the treatment compliance of tuberculosis patients. The sources obtained through search using Google Scholar, Researchget, Pubmed, and Garuda Portal, using theanalysis method SPIDER. Results: There were 9 articles related to the role of coping and adaptation to the treatment compliance of tuberculosis patients. A good coping process can trigger a response in the face of stimulus so that it will produce an adaptation function. Coping and adaptation are a unity so that the creation of adherence to the treatment of tuberculosis. Conclusion: There is a coping and adaptation assessment of the treatment compliance of tuberculosis patients in the health care center. The better the coping, the better the adaptation in tuberculosis patients so that the higher the rate of treatment adherence. Keywords: Coping, adaptation, compliance and tuberculosis.